The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/vrc2.345
|View full text |Cite
|
Sign up to set email alerts
|

Erector spinae plane block as part of a multimodal analgesic approach in an anaesthetised horse undergoing dorsal spinous process ostectomy and desmotomy

Abstract: A 14‐year‐old Irish sport horse presented to our institution with a history of right forelimb lameness and left‐sided back pain. Radiography and nuclear scintigraphy were performed under sedation and the horse was diagnosed with overriding dorsal spinous processes, also known as kissing spine syndrome. Surgical treatment consisted of dorsal spinous process ostectomy and desmotomy under general anaesthesia. This case report summarises the perianaesthetic management, which included an erector spinae plane block … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Moreover, the clinical application and efficacy of the ESP block also remain under debate, 30 and further research is needed to fully understand the mechanism of action and potential benefits of this technique. In veterinary medicine, this block has recently been investigated in several species, including dogs, 20,21 cats, 22 pigs, 19 horses 23–25 and cows 26 . Epidural spreading has been described in cadaveric studies using the US‐guided ESP block (67%), as well as the blind paravertebral (53%) techniques in cattle 26 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the clinical application and efficacy of the ESP block also remain under debate, 30 and further research is needed to fully understand the mechanism of action and potential benefits of this technique. In veterinary medicine, this block has recently been investigated in several species, including dogs, 20,21 cats, 22 pigs, 19 horses 23–25 and cows 26 . Epidural spreading has been described in cadaveric studies using the US‐guided ESP block (67%), as well as the blind paravertebral (53%) techniques in cattle 26 .…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] This block has been investigated in pigs, 19 dogs, 20,21 cats 22 and recently in horses. [23][24][25] A recent cadaveric study by d' Anselme et al 26 demonstrated the feasibility of an ultrasound-guided erector spinae plane block in cows. Compared to the traditional blind technique, the study found that the ESP block offers several advantages consistent with those reported for other facial plane blocks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This locoregional technique may be useful for desensitising the structures supplied by the dorsal rami of the thoracic and lumbar spinal nerves, specifically to identify and treat conditions affecting the spinous processes of the vertebrae. Recently, three case reports have been published demonstrating the use of ultrasound‐guided ESP (UG‐ESP) block in horses undergoing ostectomy and interspinous ligament desmotomy (Chiavaccini et al., 2022; Perez et al., 2023; Rodriguez et al., 2022). Perez et al.…”
Section: Ultrasound‐guided Nerve Blocksmentioning
confidence: 99%
“…27,30 ESP injections have recently been studied in horse cadavers, 15 and there is only one report of its clinical use in horses undergoing dorsal spinous process ostectomy and desmotomy under general anaesthesia. 16 The present case report describes the first ultrasound-guided ESP block in a standing horse as part of an opioid-free neuroleptoanalgesic protocol in a patient undergoing multiple subtotal ostectomy of dorsal spinous processes.…”
Section: Introductionmentioning
confidence: 99%